2019
DOI: 10.1186/s11671-019-3109-5
|View full text |Cite
|
Sign up to set email alerts
|

Facile Bottom-up Preparation of WS2-Based Water-Soluble Quantum Dots as Luminescent Probes for Hydrogen Peroxide and Glucose

Abstract: Photoluminescent zero-dimensional (0D) quantum dots (QDs) derived from transition metal dichalcogenides, particularly molybdenum disulfide, are presently in the spotlight for their advantageous characteristics for optoelectronics, imaging, and sensors. Nevertheless, up to now, little work has been done to synthesize and explore photoluminescent 0D WS 2 QDs, especially by a bottom-up strategy without using usual toxic organic solvents. In this work, we report a facile bottom-up strategy t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(23 citation statements)
references
References 72 publications
(86 reference statements)
2
21
0
Order By: Relevance
“…The prominent band is centered at around 275 nm, which is ascribed to the intrinsic excitonic absorption of the QDs [ 49 , 50 ]. Such a significant blue-shift of the excitonic features directly reflects the dominating quantum confinement effect and is in accordance with previous studies on other TMD QDs [ 32 , 51 ]. Furthermore, there exists another mild absorption band at longer wavelengths.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…The prominent band is centered at around 275 nm, which is ascribed to the intrinsic excitonic absorption of the QDs [ 49 , 50 ]. Such a significant blue-shift of the excitonic features directly reflects the dominating quantum confinement effect and is in accordance with previous studies on other TMD QDs [ 32 , 51 ]. Furthermore, there exists another mild absorption band at longer wavelengths.…”
Section: Resultssupporting
confidence: 92%
“…It is observed that when the excitation wavelength was increased from 290 to 400 nm, the PL peak position monotonically increased from 390 to 470 nm. Similar excitation-dependent PL behavior has been reported in a few TMD QD reports [ 32 ]. In a strong quantum confinement regime, photons with higher energies resonantly excites smaller QDs with wider band gaps, pushing the emission peak to shorter wavelengths.…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…CDs/MoS 2 exhibited good catalytic activity for the hydrogen evolution reaction with high cathodic current density and a positive onset over-potential of~0.109 V. Surprisingly, even better performance was observed when the CD/MoS 2 catalyst was exposed to visible light for 30 min. Recently, hybrid CDs/tungsten disulfide quantum dots (CDs/WS 2 QDs) have been prepared from sodium tungstate dihydrate and l-cysteine by a bottom-up hydrothermal method and were used as a luminescent probe for the detection of H 2 O 2 and the enzymatic sensing of glucose [70].…”
Section: Modification Of Cds For Photocatalysismentioning
confidence: 99%
“…The presence of hydrogen peroxide resulted in the quenching of WS 2 QDs fluorescence, proportional to the analyte concentration. 194 The quenched fluorescence of Rhodamine-B by sulfur doped graphene oxide was used as the sensing signal for the detection of hydrogen peroxide. The limit of detection for this system was as low as 100 pM.…”
Section: D Layered Materials Based (Bio)sensors For Oxidative Stress ...mentioning
confidence: 83%